Utilizing electromyography to identify causes of exhaustion in pigs fed ractopamine-HCL - Noel, Jere Annabella (Kansas State University, 2016)
Pigs fed ractopamine-HCl (RAC) are more prone to fatigue and exhaustion when improperly handled. Wireless electromyography (EMG) can be used to directly measure median power frequency (MdPF) and root mean square (RMS) as indicators of action potential conduction velocity and muscle fiber recruitment, respectively. The objectives of this study were to determine the effect of RAC on exhaustion, EMG measures, and muscle fiber type characteristics when barrows were subjected to increased levels of activity. Thirty-four barrows were assigned to one of two treatments: a commercial finishing diet containing 0 mg/kg (CON) RAC or a diet formulated to meet the requirements of finishing barrows fed 10 mg/kg RAC (RAC+) for 35 d. After 32 d of feeding, barrows were walked around a circular track at 0.79 m/s until subjective exhausted was reached. Time, distance, and speed were measured. Wireless surface EMG sensors were affixed to the Deltoideus (DT), Triceps brachii lateral head (TLH), Tensor fasciae latae (TFL), and Semitendinosus (ST) muscles. After harvest, samples of each muscle were collected for fiber type, succinate dehydrogenase, and capillary density analysis. Speed was not different (P = 0.82) between treatments, but RAC+ barrows reached subjective exhaustion quicker and covered less distance than CON barrows (P < 0.01). The end-point MdPF was not affected by the RAC diet. The RAC diet did not change end-point RMS values in the DT or TLH; however, the RAC+ barrows tended to have decreased ST and increased TFL end-point RMS values (P < 0.07). The percentage of type I fibers tended to be greater (P = 0.07) in RAC+ barrows, but the RAC diet tended to increase (P = 0.07) size of type I fibers and increase (P = 0.03) the size of type IIA fibers. Succinate dehydrogenase was not different between treatments. The RAC+ barrows had more (P = 0.03) capillaries per fiber than CON barrows. A diet containing RAC contributes to increased onset of subjective exhaustion, possibly due to rapid loss of active muscle fibers and chronic loss of oxidative muscle fibers with no change in muscle metabolism.
Keywords: Electromyography; Pig; Exhaustion; Fiber type; Ractopamine-HCl